Dedicated protection scheme for optical networks survivability - S. N. F., Halida (IEEE Explorer, 2011)
In recent days, optical fibers have been developed as a transmission medium to carry traffic in order to provide various services in telecommunications platform. Failure of this fibre caused loss of data which can interrupt communication services. Thus, this paper will focus about protection scheme in order to guarantee the survivability of the networks. Besides, the scheme should provide better quality of services (QOS) in terms of network resource usage, connection availability satisfaction ratio (ASR) and blocking probability. A sample of mesh torus network was carried out to compare several basic connection management processes and dedicated protection scheme was taken into consideration. Matlab was used as a simulation platform in this project. Analyze for performance metrics will shown that there are significant improvements of availability satisfaction Ratio (ASR) when dedicated path protection is utilized in optical network. This project provides an insight of advanced in protection scheme and can serve as a foundation for future research.